An unusual cause of abdominal pain. (25th January 2011) - Mc Cabe, Aileen; Low, Justin; McInerney, John
Abstract : A 26-year-old man presented to the Emergency Department with abdominal pain, diarrhoea, anorexia and haematemesis. The patient was previously diagnosed with latent tuberculosis (TB). On examination, his abdomen was diffusely tender, with localised guarding in the right iliac fossa. CT imaging of his abdomen and pelvis demonstrated a low volume of ascites, diffuse studding of the peritoneum, omental caking and several bulky low-density lymph nodes in the retroperitoneum. A laparoscopy was performed to obtain a peritoneal biopsy. Histology demonstrated fragments of peritoneum with necrotising granulomatous inflammatory infiltrate in keeping with an infectious process, favouring TB. He was commenced on rifampicin, isoniazid, pyrazinamide, ethambutol and pyridoxine under the direct observed therapy by the infectious diseases team. In view of his extensive peritoneal involvement, he was empirically started on high-dose prednisolone for symptomatic control and to reduce complications related to peritoneal adhesions.